The Muslimist Self and Fashion: Implications for Politics and Markets - Cevik, Neslihan (Numen, 2019)
This article introduces the rise of a new religious expression, Muslimism, in Turkey at the turn of the 21st century. I identify Muslimism as a prominent example of a new global category of religion, New Religious Orthodoxies (NRO). Muslimism and NROs neither reject nor submit to global modernity but engage aspects of it using religious categories. I then link Muslimism and NROs to the broader discussions on Muslim subjectivity formation, looking at Islamic fashion and how Muslimists respond to global modernity and its imaginaries, practices, and institutions. My empirical findings show that, historically, Islamic fashion has functioned as a site of hybridity, allowing pious Muslim females to resist binary patterns of identity, public space, and everyday activities, to challenge authoritarian formulations of religious community and redefine the (female) self as a legitimate moral and cultural agent by tapping into key Islamic notions. These findings have broad implications. Theoretically, they show that even in an area such as Islamic fashion, reduced by many as an oxymoron created by market forces, Muslim subjectivity formation goes beyond the choices of rejection of modernity or assimilation of Islam. Mapping these possibilities reveals greater insights into how religious groups engage modernity while remaining within the limits of orthodoxy, as well as their potent agency in challenging existing sources of self-formation and collective identity. Regarding policy, Muslimism illustrates a third way between fundamentalism and aggressive secularism that can negotiate tensions between religious orthodoxy and individual rights, the secular state and moral freedoms, and the West and Islam.